Potential of Chlorella sp As A Bioremediation Agent in Tofu Liquid Waste: Literature Review - Surya Eka Putra; Threo Wanda Marten; Elsa Yuniarti; Linda Handayani (Jurnal Biologi Tropis, 2023)
Tofu liquid waste that contains high levels of COD (Chemical Oxygen Demand), BOD (Biological Oxygen Demand), and TSS (Total Suspended Solid) is usually discharged directly into the waters, causing a foul odor in community drainage and contaminating rivers. This study aims to determine the potential of Chlorella sp as a bioremediation agent in tofu wastewater. This type of research is research that uses the literature review method. The stages of literature collection used in this study refer to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. This stage consists of four procedures, namely, identification, screening, eligibility, and acceptance. This study shows that the microalgae Chlorella sp. can increase population growth and lipid levels, Chlorella sp. Can reduce COD and Nitrate levels contained in tofu liquid waste, and increase the pH from acidic to neutral. Based on the results of the study found, it can be concluded that Chlorella sp has the potential as a bioremediation agent in tofu liquid waste.